Mastering Supply Chain Risks - Jereb, Borut; Cvahte, Tina; Rosi, Bojan (Serbian Journal of Management, 2012)
Risks in supply chains represent one of the major business issues today. Since every organization strives for success and uninterrupted operations, efficient supply chain risk management is crucial. During supply chain risk research at the Faculty of Logistics in Maribor (Slovenia) some key issues in the field were identified, the major being the lack of instruments which can make risk management in an organization easier and more efficient. Consequently, a model which captures and describes risks in an organization and its supply chain was developed. It is in accordance with the general risk management and supply chain security standards, the ISO 31000 and ISO 28000 families. It also incorporates recent finding from the risk management field, especially from the viewpoint of segmenting of the public. The model described in this paper focuses on the risks itself by defining them by different key dimensions, so that risk management is simplified and can be undertaken in every supply chain and organizations within them. Based on our mode and consequent practical research in actual organizations, a freely accessible risk catalog has been assembled and published online from the risks that have been identified so far. This catalog can serve as a checklist and a starting point in supply chain risk management in organizations. It also incorporates experts from the field into a community, in order to assemble an ever growing list of possible risks and to provide insight into the model and its value in practice.
Keywords: ISO; mastering; supply chain; Risk management